Perkembangan Kota Gunungsitoli Tahun 2008-2024 - Novi Kristina Telaumbanua; Najmi Najmi (Jurnal Kronologi, 2026)
Gunungsitoli is the only city on Nias Island that was officially established as an autonomous city through Law Number 47 of 2008. Since then, the city has experienced significant developments in economic, infrastructural, and socio-cultural aspects. This study aims to analyze the background of the establishment of Gunungsitoli as a result of the administrative division from Nias Regency and to examine the city's development from 2008 to 2024. This research employs the historical research method consisting of four stages: heuristics, source criticism, interpretation, and historiography. The findings indicate that the establishment of Gunungsitoli was influenced by local government policies, the strong aspirations of the Nias community to obtain better public services, and the support of the Nias Regency government. Since its inauguration, Gunungsitoli has experienced rapid development in various sectors, marked by the completion of the government center in 2016, the revitalization of three major markets (Pasar Nou, Pasar Gomo, and Pasar Soliga), improvements and expansion of the road network reaching all six districts, the development of Gunungsitoli (Angin) Port and Binaka Airport as regional transportation facilities, as well as the increase in educational, health, and housing facilities. By 2024, development had reached all areas of Gunungsitoli, although it had not been entirely evenly distributed, as the central urban areas continued to develop more rapidly than peripheral areas, particularly Idanoi District and Gunungsitoli Alo'oa District. This development accelerated following the inauguration of the first definitive mayor in 2011 and continued through 2024. Nevertheless, challenges remain, including regional development disparities and the need to improve human resource quality and ensure sustainable governance.